Analysis of Service Quality and Price Aspects on Patient Satisfaction at Gorontalo Regional Hospital - Dama, Desi Putri; Darman, Darman; Rachman, Azis; Patuti, Zeinia (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to examine the factors influencing patient satisfaction at Gorontalo Hospital, focusing on the impact of service quality and price. Using primary data from 108 respondents gathered via Google Form through purposive sampling, the analysis employs Partial Least Square - Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The research model is developed using the Confirmatory Composite Analysis approach, with indicators based on established theories. The outer model evaluates instrument validity and reliability, using Average Variance Extracted (AVE) for convergent validity and Composite Reliability (CR) and Cronbach’s Alpha for reliability. Both research hypotheses were supported, with Service Quality showing a significant positive effect on Patient Satisfaction, and Price also having a significant positive effect on Patient Satisfaction. These findings align with previous studies, emphasizing the importance of service quality and price in enhancing patient satisfaction. The study contributes to the formulation of more effective strategies to improve healthcare services and pricing transparency, ultimately aiming to enhance patient experiences and satisfaction at Gorontalo Hospital.